Kierunki racjonalizacji struktury rolnictwa polskiego w świetle rozwiązań stosowanych w Europie Zachodniej - BABIAK, Jerzy (Przegląd Politologiczny, 2018)
Agriculture is a peculiar sector of the economy that requires support from the state. Its spontaneous transformation is not effective enough, therefore a number of mechanisms are applied to stimulate advantageous structural transformation both at EU and national levels. The agricultural system of West European states is based on the family farm. Although Community law does not define a family farm, different systems provide various measures applied in order to protect family farms, e.g. by means of controlling agricultural land trade. The paper presents the legal and institutional solutions applied in this respect in France, Germany and Denmark. These states have not been randomly selected, as they are the main competitors for Polish agriculture in the Community market, and they have succeeded in establishing an agrarian structure. Against the background of their experience, Polish legal solutions are presented and assessed. The responsibilities of the Agricultural Property Agency are presented in detail; its principal task apart from the management of State Treasury property is to shape agrarian structure.